Respuesta :
To distribute this, multiply each term in the parentheses by -12
-12(4x) + -12(5y)
-48x - 60y
Hope this helps :)
Comment if you need any more explanation
Answer:
-48x - 60y
Step-by-step explanation:
Distributive Property of multiplication over addition:
[tex]\boxed{a(b + c) = ab + ac}[/tex]
Apply the distributive property to the given expression:
[tex]\begin{aligned}-12(4x + 5y) & = -12 \cdot 4x + (-12) \cdot 5y\\& = -48x +(- 60y)\\&=-48x-60y\end{aligned}[/tex]
Therefore, the given expression rewritten using distribution is:
- -48x - 60y